UJI EFEK ANTIDIARE EKSTRAK RIMPANG KUNYIT (Curcuma domestica val.) PADA MENCIT JANTAN - Linta Meliala; Winda Sari; Palas Tarigan (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2020)
Objectives : The purpose of this study to determine the effect and dose of effective use of rhizome extract of turmeric as antidiarrhea in male mice induced castor oil and the use of rhizome extract of turmeric equivalent to Loperamid HCl. Method : This research method is carried out experimentally with the research stages of sample preparation, sample characterization, simplicia screening, preparation of extracts, preparation of animal experiments and testing of antidiarrheal effects in experimental animals. Results : The results showed that the results of phytochemical screening of simplicia powder and turmeric rhizome extract contained flavonoids and tannins. SPSS statistical test results (statistical package for the social science) continued with defference test of Duncan average, the duration of the occurrence of diarrhea showed that the control group of Loperamid HCl dose 1 mg/kg bw gave significant effect on turmeric rhizome extract at doses of 40 mg/ kg bw and doses 80 mg/kg bw. The shorter the time of diarrhea, the stronger the antidiarrheal effect. Conclusion : Turmeric rhizome extract dose 20 mg/kgbw showed that dose 20 mg/kgbw has antidiarrhea effect more than lower than Loperamid HCl dose 1 mg/kg bw. Turmeric rhizome extract dose 40 mg/kg bb has same effect with Loperamid HCl dose 1 mg/kgbb. And turmeric rhizome extract dose 80 mg/kgbb has effect more potencial that Loperamid HCl dose 1mg/kg bw. There is a relationship between the size of the dose with the antidiarrheal effect that occurs.